2003
DOI: 10.1016/s0006-3495(03)70060-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Gramicidin Interactions: Dynamic Structure of the Boundary Lipid by 2D-ELDOR

Abstract: The use of 2D-electron-electron double resonance (2D-ELDOR) for the characterization of the boundary lipid in membrane vesicles of DPPC and gramicidin A' (GA) is reported. We show that 2D-ELDOR, with its enhanced spectral resolution to dynamic structure as compared with continuous-wave electron spin resonance, provides a reliable and useful way of studying lipid-protein interactions. The 2D-ELDOR spectra of the end-chain spin label 16-PC in DPPC/GA vesicles is composed of two components, which are assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
(103 reference statements)
2
45
0
Order By: Relevance
“…It is important to note that in all three steps (i, ii, and iii) a set of 2D-ELDOR spectra for several mixing times, T m are simultaneously fit [3,[6][7][8][9][10][11]. In the full S cÀ method, this set of spectra vs. T m are fit to the same phase corrections, since all the experimental settings are kept constant, except for T m .…”
Section: The Full S Cà Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that in all three steps (i, ii, and iii) a set of 2D-ELDOR spectra for several mixing times, T m are simultaneously fit [3,[6][7][8][9][10][11]. In the full S cÀ method, this set of spectra vs. T m are fit to the same phase corrections, since all the experimental settings are kept constant, except for T m .…”
Section: The Full S Cà Methodsmentioning
confidence: 99%
“…For example, using spin-labeled lipids, it was shown that 2D-ELDOR displays significantly different spectra for the liquid-ordered (L o ) phase vs. the liquid-disordered (L d ) phase, and thus provides a visual distinction of these two important phases [10], since they may be related to the main components found in biomembranes. In another study [11], involving membranes of peptide dissolved in lipid, it was unequivocally shown that there are two distinctly different spectral components, respectively, representing bulk and boundary lipids which coexist [19,20].…”
Section: D-eldormentioning
confidence: 99%
See 1 more Smart Citation
“…The more motionally restricted component (b) is usually assigned to the boundary lipids contacting the GA aggregates [22][23][24][25], in analogy with similar studies on integral transmembrane proteins [26]. The weakly immobilized component (f) corresponds to the fluid (free) lipids, although the EPR spectra of the latter indicate considerably lower rotational mobility as compared with membranes of fluid lipids alone.…”
Section: Lipid-peptide Complexes: Interaction Of Gramicidin a With Dmmentioning
confidence: 79%
“…In previous studies [22][23][24][25], mostly on membranes with rather high gramicidin A contents (GA/lipid P 0.1 mol/mol), it was found that the conventional low-power EPR absorption spectra of phospholipids spin-labelled close to the terminal methyl group of the sn-2 chain contain two components. The more motionally restricted component (b) is usually assigned to the boundary lipids contacting the GA aggregates [22][23][24][25], in analogy with similar studies on integral transmembrane proteins [26].…”
Section: Lipid-peptide Complexes: Interaction Of Gramicidin a With Dmmentioning
confidence: 99%